Acute effects of static and proprioceptive neuromuscular facilitation stretching on agility performance in elite youth soccer players - Jordan, J. B.; Korgaokar, A. D.; Farley, R. S.; Caputo, J. L. (International Journal of Exercise Science, 2012)
A warm-up is an important part of preparation for a soccer match. Stretching is typically part of the warm-up however, debate exists as to the most appropriate type of stretching to perform. The purpose of this study was to examine the effects of static and proprioceptive neuromuscular facilitation (PNF) stretching on soccer-specific agility performance in 14 male elite, premier league youth soccer players. Participants completed 4 trials of the Balsom agility test while dribbling a soccer ball. Height, age, and body mass were collected in trial 1 and participants were accommodated to the agility test during trials 1 and 2. Trials 3 and 4 were the static and PNF treatment trials that were administered after a standardized warm-up (control) in a randomized and counterbalanced manner. There were no significant differences between the difference scores of the static and PNF stretching conditions, P = .66. Furthermore, no significant differences were found between the control and stretching trials for static stretching, P = .15 or between the control and stretching trials for PNF stretching, P = .58. Neither mode of stretching significantly affected agility performance. More research is needed to determine the chronic effects of PNF stretching on agility performance.